Numerical simulation of hydrogen-aided diesel engine - Tan, Shuwen (2017)
The purpose of this project is to perform numerical simulations of a hydrogen-aided diesel engine and find out if adding hydrogen to the engine system is beneficial in terms of combustion efficiency and environmental effects, such as NOx and COx footprint.